SENSITIVITY OF ACTIVE PHASED ANTENNA ARRAY ELEMENT OF GURT RADIO TELESCOPE - P. L. Tokarsky (Radio Physics and Radio Astronomy, 2016)
Purpose: theoretical and experimental investigations of sensitivity by the signal-to-noise ratio criterion active antenna used as a phased array element of the GURT radio telescope of new generation.